Obtención de bebida alcohólica tipo vino de frutas a base de arándano azul (Vaccinium corymbosum) y feijoa (Acca sellowiana). - Pilapanta Bombon, Joselin Michelle (2022)
The objective of the research was to obtain an alcoholic beverage type fruit wine based on blueberry (Vaccinium corymbosum) and feijoa (Acca sellowiana), in order to generate added value to these raw materials, for which treatments were established. , being factor A, the concentration of blueberry and feijoa pulp in different proportions (30% A - 70% F) (50% A - 50% F) (70% A - 30% F); factor B, the applied nutrients (Fermaid k 100%) (Go ferm protect evolution 100%) (Fermaid k 50% + Go ferm protect evolution 50%), using a completely randomized block design (DBCA) in a 3x3 factorial arrangement with two repetitions with a total of 18 treatments subjected to fourteen days of fermentation, where physical chemical parameters were evaluated (Soluble solids, alcoholic degrees and pH), at soluble solids and pH variables, the best treatment cannot be identified because they do not present significance, while at alcoholic degrees the best treatment corresponding to t₁ (50% blueberry - 50% feijoa / Fermaid k nutrient) was determined. obtaining the best treatment, resulting in the t₁ corresponding to (50% blueberry + 50% feijoa / Fermaid k nutrient). Physicochemical analyzes were carried out which the following results were obtained: Alcoholic degrees 10 GL, Volatile acidity 0.19 g/L, Total sulfur dioxide 66.82 mg/L, Methanol 11.35 mg/100 cm³ AA and Total sugars 7.99%, in accordance with the established parameters at NTE INEN 374, alcoholic beverages, fruit wine, with respect to microbiological analysis, a mold count <10 CFU/ml was obtained, in accordance with established parameters by NTE INEN 2802, alcoholic beverages, cocktails or mixed alcoholic beverages and appetizers, while the yeast count 30 CFU/ml is not within established limits. Finally, for a production of $107.36, the unit cost of fruit wine production is $5.37, the RRP is $6.98 for each bottle of fruit wine in a 750 ml presentation.